Assessment of non photochemical quenching from conformational changes in CP29 - Παπαδάτος, Σωτήριος Διονύσιος (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, 2016)
Photosynthesis is characterized as one of the most important processes on earth. Light is harvested by pigments bound in complexes, situated in organelles called chloroplasts. The harvested energy is converted to electrons, which fuel the plant’s metabolic cycle to produce ATP. During this process plants also accumulate carbon dioxide and produce organic forms of carbon, which in turn is the foundation of all life. During their evolutionary history plants have evolved mechanisms to cope with the variations of light intensity and climate. The various mechanisms apart from light intensity are also triggered by duration, ranging from the short term acclimations that occur in matter of seconds like changes in the electron flow to adaptations of a specie. One of the mechanisms is Non Photochemical Quenching (NPQ), in which plants remove the excess of solar radiation as heat. Although plants and their defense mechanisms have been thoroughly studied the exact nature of NPQ is still elusive. In this essay, with the use of computer simulations, a potential role of certain protein complexes (CP29) is examined, that NPQ is triggered by conformational changes due to a pH gradient.
Keywords: Photosynthesis; Chloroplasts; Dioxide